2002
DOI: 10.1021/jf026006k
|View full text |Cite
|
Sign up to set email alerts
|

Shikimate Accumulates in Both Glyphosate-Sensitive and Glyphosate-Resistant Horseweed (Conyza canadensis L. Cronq.)

Abstract: Horseweed (Conyza canadensis) is a cosmopolitan weed that commonly grows throughout North America. Horseweed that is not completely controlled by normal applications of glyphosate has been reported in western Tennessee. This research had three objectives: (1) to develop and validate an analytical procedure for the quantitative determination of shikimate, an important indicator of glyphosate activity in plants; (2) to confirm resistance to glyphosate in a horseweed population; and (3) to examine the accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
145
0
9

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(162 citation statements)
references
References 20 publications
8
145
0
9
Order By: Relevance
“…These results are similar to those found in the literature, in which resistant and susceptible biotypes of C. canadensis to glyphosate present accumulation of shikimic acid (Mueller et al, 2003;Feng et al 2004). In Conyza sp.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results are similar to those found in the literature, in which resistant and susceptible biotypes of C. canadensis to glyphosate present accumulation of shikimic acid (Mueller et al, 2003;Feng et al 2004). In Conyza sp.…”
Section: Resultssupporting
confidence: 92%
“…stalled the growth of the susceptible biotype by 57%, while for the resistant biotype DM was not affected (Table 1). A similar result was observed by Mueller et al (2003), when resistant biotypes of Conyza canadensis showed stoppage of increment of DM by about 40% after application of 840 g ha -1 and glyphosate e.a., while the susceptible biotypes showed a drop of more than 80% at 17 DAH.…”
Section: Resultssupporting
confidence: 84%
“…Singh & Shaner (1998) and Mueller et al (2003) reported recoveries higher than 80% of spiked shikimic acid in crude extracts of soybean, maize and horseweed. Recoveries of 100% of shikimic acid in spiked samples of cotton, and 85% to 104% in fortified wheat tissue were also reported by Pline et al (2002) and Anderson et al (2001), respectively.…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, other shikimic acid methods use various reagents such as sulfuric acid (Harring et al, 1998), HCl (Mueller et al, 2003) and alcohols (Anderson et al, 2001;Jaroszynska 2003). Our method provides close to 100% extraction efficiency and a high level of sensitivity without interference with other compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation